IMPLEMENTASI METODE AHP DAN SAW DALAM PEMILIHAN GURU TERBAIK DI SMK PLUS MUNIRUL ARIFIN NW PRAYA - Husnul Khotimah; Mohammad Taufan Asri Zaen; Khairul Imtihan (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
SMK Plus Munirul Arifin NW Praya is an educational institution under Munirul Arifin NW Praya Foundation which is located in Central Lombok. SMK Plus Munirul Arifin NW Praya is a formal education which has a role in improving the quality of education, so the role of teachers is very important to achieve this goal. Therefore, the quality of teachers also greatly influences the achievement of quality education. To improve teacher performance, the principal wants to give appreciation who have the best performance. This research uses a combination of two methods, namely the AHP and SAW methods, where the AHP method is used to determine the weight of each criterion and the SAW method is used to determine the solution to the problem, namely determining the best teacher by ranking. In determining the weight of the criteria using the AHP method, the weight for each criterion is produced, namely Loyalty at 43%, Discipline at 21%, Pedagogy at 12%, Personality at 20%, and social at 4%. Then the results of the ranking carried out using the SAW method produce a ranking. First place was achieved by Alternative 1 in the name of Amruzziyad with a total score of 0.96